Nuclear receptor coregulator NRIP1 R448G modulates T cell gut homing to control intestinal inflammation - Xiangjun Chen; Hee Seung Hwang; Bihua Li; Yanhua Zhao; Koushik Ghosh; Lei Deng; Elizabeth A. Creasey; Orr Ashenberg; Daniel B. Graham; Ramnik J. Xavier (Proceedings of the National Academy of Sciences, 2025)
Nuclear receptors (NRs) are crucial to integrate metabolite sensing and immune responses in the gut. NR-interacting protein 1 (NRIP1) is an important coregulator of various NRs that has been implicated in inflammatory bowel disease risk, but mechanistic details of how NRIP1 controls NR activities mediating immune homeostasis and inflammation remain elusive. We demonstrate that a missense risk variant, NRIP1 R448G, promotes activated CD4 + T cell gut homing and inflammatory cytokine production, ultimately leading to exacerbated intestinal inflammation. Mechanistically, NRIP1 acts as a corepressor in retinoic acid signaling by expression of a gut-homing transcriptional program. Our study reveals the impacts of NRIP1 on CD4 + T cells in immune regulation during intestinal inflammation, providing insights into mechanisms by which an NR coregulator controls immune homeostasis and tissue inflammation.